Why medical students choose psychiatry - A 20 country cross-sectional survey - Farooq, K.; Lydall, G.J.; Malik, A.; Ndetei, D.M.; ISOSCCIP Group; Bhugra, D.; Alemu, Y.B.; Ohene, S.; Mathai, M.; Gakinya, B.; Uwakwa, R.; Olugbile, F.; et al. (BMC Medical Education, 2014)
Recruitment to psychiatry is insufficient to meet projected mental health service needs world-wide. We report on the career plans of final year medical students from 20 countries, investigating factors identified from the literature which influence psychiatric career choice. Methods. Cross sectional electronic or paper survey. Subjects were final year medical students at 46 medical schools in participating countries. We assessed students' career intentions, motivations, medical school teaching and exposure to psychiatry. We assessed students' attitudes and personality factors. The main outcome measure was likelihood of specializing in psychiatry. Multilevel logistic regression was used to examine the joint effect of factors upon the main outcome. Results: 2198 of 9135 (24%) of students responded (range 4 to 91%) across the countries. Internationally 4.5% of students definitely considered psychiatry as a career (range 1 to 12%). 19% of students (range 0 to 33%) were "quite likely", and 25% were "definitely not" considering psychiatry. Female gender, experience of mental/physical illness, media portrayal of doctors, and positive attitudes to psychiatry, but not personality factors, were associated with choosing psychiatry. Quality of psychiatric placement (correlation coefficient = 0.22, p < 0.001) and number of placements (correlation coefficient =0.21, p < 0.001) were associated with higher ATP scores. During medical school, experience of psychiatric enrichment activities (special studies modules and university psychiatry clubs), experience of acutely unwell patients and perceived clinical responsibility were all associated with choice of psychiatry. Multilevel logistic regression revealed six factors associated with students choosing psychiatry: importance of own vocation, odds ratio (OR) 3.01, 95% CI 1.61 to 5.91, p < 0.001); interest in psychiatry before medical school, OR 10.8 (5.38 to 21.8, p < 0.001); undertaking a psychiatry special study module, OR 1.45 (1.05 to 2.01, p = 0.03) or elective OR 4.28 (2.87- 6.38, p < 0.001); membership of a university psychiatry club, OR 3.25 (2.87 to 6.38, p < 0.001); and exposure to didactic teaching, OR 0.54 (0.40 to 0.72, p < 0.001). Conclusions: We report factors relevant to medical student selection and psychiatry teaching which affect career choice. Addressing these factors may improve recruitment to psychiatry internationally. © 2014 Farooq et al.; licensee BioMed Central Ltd.
Keywords: Attitude to psychiatry; Career choice; Enrichment activity; Gender; Medical school selection; Medical student; Psychiatry; Recruitment; Stigma